EVALUATION OF EQUILIBRIUM CORE OPERATION OF THE RSG-GAS REACTOR - Iman Kuntoro; Surian Pinem; Tagor Malem Sembiring; Dwi Haryanto; Sigit Purwanto (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2021)
The Indonesian Multipurpose Reactor, RSG-GAS reactor will accomplish its first lifetime in December 2020. The reactor has been operated in safe and reliable manner for about 33 years since it commenced in operation in 1987 to serve radioisotopes production, NAA, neutron beam experiments, material irradiation, and reactor physics experimental activities as well as training. The paper is intended to evaluate its in-core fuel management that is the conformance between the theory and implementation of the equilibrium core. Evaluation of the reactor operation parameter was carried out for core numbers 91 – 100. The data show that excess reactivity, shutdown reactivity and control rod reactivity have no significant difference at each core. The result shows that the BATAN-FUEL accurately determine the equilibrium core and its fuel loading pattern.This in-core fuel management of the RSG-GAS reactor supports the safety of reactor operation.